Early initiation of breastfeeding at Dustira Hospital - Yoke Ayukarningsih; Arief Dwinanda (Indonesian Pediatric Society Publishing House, 2015)
Background The infant mortality rate (IMR) in Indonesia is higher than that in other ASEAN countries. The highest rate of mortality occurs in the first 24 hours of life. Suboptimal breastfeeding initiation is a cause of high IMR. In an effort to decrease infant mortality, implementing early initiation of breastfeeding (EIB) has been encouraged. Objective To assess the success rate and time needed for latching on in EIB implementation. Methods We reviewed medical records of vaginal deliveries at Dustira Hospital, Cimahi, West Java, from June-November 2011. Results From 305 vaginal deliveries, 174 infants received EIB, though only 159 medical records could be assessed. The results showed that 52 % did EIB with a 91.8% success rate (defined as good implementation by WHO) and a 8.2% fail rate. In terms of subjects' birth weights, the success rate of EIB implementation was 62.5% in the low birth weight (LBW) group, 94.9% in the normal birth weight (NBW) group, and 100% in the large birth weight or macrosomic group. The success rate of EIB implementation was 69.2% in the preterm group and 93.8% in the full term group. The success rate of EIB implementation was 71.4% in the LBW/fullterm group and 55.6% in the LBW/preterm group. The amount of time for infants to latch on was highest within the 30-44 minute group (52.7%). Conclusion The EIB implementation at Dustira Hospital was classified as good and the amount of time to latch on was 30-44 minutes.